Indicators for the evaluation of the stock market on trading platforms NYSE and NASDAQ (Journal of Economic Research & Business Administration, 2016)
The article discusses the technique of investing in stocks, namely,what indicators to consider when investing in this instrument. As the objectof the analysis were used trading platforms NYSE and NASDAQ. Themain indicators have been proposed stock index, the market capitalizationof the company, the rate of earnings per share and beta coefficient. The lastfactor will help the investor to predict the level of risk of a particular stock.High dynamics of development of the stock market makes it necessaryto find new and effective management practices. The method of analysis ofmarket indicators will serve as a reference point in the direction of the marketand the stock assessment. After all, the forecast growth rate or falling actionis not always possible to predict with accuracy. It’s no secret, the emergenceof rating agencies help investors and professional participants in the selectionof issuers of debt securities. Therefore, the publication of the values of “beta”factor also gives investors more advantages in investing in shares. Comparingthe values of the indicators, the investor share comfortably to rank level of riskand select an action in accordance with the wishes of investors.
Keywords: investing in stocks; stock index; the market capitalization of the company; the rate of earnings per share and beta coefficient.